2018
DOI: 10.1093/pcp/pcy155
|View full text |Cite
|
Sign up to set email alerts
|

α-Expansin EXPA4 Positively Regulates Abiotic Stress Tolerance but Negatively Regulates Pathogen Resistance in Nicotiana tabacum

Abstract: Since they function as cell wall-loosening proteins, expansins can affect plant growth, developmental processes and environmental stress responses. Our previous study demonstrated that changes in Nicotiana tabacum α-expansin 4 (EXPA4) expression affect the sensitivity of tobacco to Tobacco mosaic virus [recombinant TMV encoding green fluorescent protein (TMV-GFP)] infection by Agrobacterium-mediated transient expression. In this study, to characterize the function of tobacco EXPA4 further, EXPA4 RNA interfernc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…The overexpression of TaEXPA2 in tobacco and wheat enhanced drought tolerance in the transgenic plants (Chen et al, 2016;Yang et al, 2020). Moreover, improved tolerance to salinity and drought was also shown in tobacco plants overexpressing the tobacco EXPA4 (Chen et al, 2018). In barley, HvEXPB7 improved the growth of barley root hairs under drought in the drought tolerant Tibetan wild barley genotype (He et al, 2015).…”
Section: A Beta-expansin Gene Was Uniquely and Highly Induced In Otismentioning
confidence: 89%
“…The overexpression of TaEXPA2 in tobacco and wheat enhanced drought tolerance in the transgenic plants (Chen et al, 2016;Yang et al, 2020). Moreover, improved tolerance to salinity and drought was also shown in tobacco plants overexpressing the tobacco EXPA4 (Chen et al, 2018). In barley, HvEXPB7 improved the growth of barley root hairs under drought in the drought tolerant Tibetan wild barley genotype (He et al, 2015).…”
Section: A Beta-expansin Gene Was Uniquely and Highly Induced In Otismentioning
confidence: 89%
“…Similarly, as presented by Abuqamar et al [16], the downregulation or knockdown of AtEXLA2 enhanced resistance to the necrotrophic fungus Alternaria brassicicola. Furthermore, the EXPA4 gene negatively regulated the defense response against TMV in N. benthamiana [17] but enhanced abiotic stress tolerance [18]. However, aside from a role in plant abiotic stress, the influence of the EXPA3 gene on plant-pathogen interactions was well-documented, but only for the Arabidopsis-cyst nematode pathosystem, by Wieczorek et al [19].…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed that transgenic plants with altered EXPA4 demonstrated that RNAi mutants have increased hypersensitivity to salt and drought stress and vice-versa in overexpressed tobacco lines, consequently, leading to lower cell damage, higher fresh weight, soluble sugar, proline accumulation, and induces several stress responsive gene expression. Therefore, EXPA4 indicated its involvement in salt and drought stress response via changes in the expression levels of some stress-responsive genes ( Chen et al, 2018 ). Moreover, downregulation of arabinogalactan proteins ( AGPs ) was also seen in our study.…”
Section: Discussionmentioning
confidence: 99%